Participação dos neurônios noradrenérgicos da região A5 no controle cardiorrespiratório durante a hipercapnia e hipóxia em ratos - Taxini, Camila Linhares (2012)
The noradrenergic A5 group is an important group of neurons located in the ventrolateral pons and receives projections from several medullar areas related to cardiorespiratory regulation. The A5 region contributes to the maturation of the respiratory system before birth and in adult rats these neurons are connected with the neural network responsible for respiratory rhythmogenesis. The A5 neurons have an important involvement in autonomic control, these neurons send and receive projections from various regions involved in cardiovascular control, and send projections directly to the intermidial column lateral. Thus, we tested the hypothesis that noradrenergic neurons of A5 region participate in cardiorespiratory responses produced by hypercapnia or hypoxia in anesthetized and ananesthetized rats. In ananesthetized animals without and sino-aortic denervation, the lesion of the noradrenergic neurons in the A5 region with anti-dopamine β-hydroxylase-saporin (anti-DβH-SAP, 4.2 ng) promoted a decrease of tidal volume response to acute hypercapnia (7% CO2, 30 minutes) and acute hypoxia (7% O2, 30 minutes), but did not alter the cardiovascular response. In anesthetized animals during the acute hypercapnia (5% to 10% CO2, 5 minutes), the bilateral microinjection of muscimol (GABA-A agonist; 2 mM) and the chemical injury with anti-DβH-SAP on the A5 region reduced the increase of mean arterial pressure (MAP), splanchnic sympathetic activity (sSNA), frequency and amplitude of phrenic nerve produced by hypercapnia. During acute hypoxia (8-10% O2, 30 seconds) the bilateral microinjection of muscimol in the A5 region attenuated the increase in MAP and sSNA promoted by hypoxia without affecting the activity of the phrenic nerve, but the chemical injury of A5 region not altered responses promoted by hypoxia. The results of this study show that the participation of the A5 region in cardiorespiratory response depends on the animal's condition, anesthetized or not, as well as CO2 and O2 levels. In animals ananesthetized, the noradrenergic neurons of A5 region exert an excitatory modulation in control of tidal volume in response to hypercapnia and hypoxia. While in anesthetized animals, this region stimulates the cardiorespiratory response to hypercapnia, increasing the amplitude and frequency of the phrenic nerve, and sympathetic activity.